Manfaat Aplikasi E-ProfBid Terhadap Pengetahuan Ketrampilan Klinis Asuhan Kebidanan Pada Persalinan - Durrotun Munafiah; Dewi Mayangsari; Maftuchah Maftuchah; Hermeksi Rahayu; Hargokendar Suhud; Mariza Mustika Dewi (Politeknik Kesehatan Kementrian Kesehatan Semarang, 2024)
Midwives are responsible and accountable professionals, who work as women's partners to provide support, care and advice during pregnancy, labor and the postpartum period, facilitate childbirth on their own responsibility and provide care for newborns and infants. Midwives, as one of the oldest professions in the world, have a very important and strategic role in reducing MMR and IMR as well as preparing a quality next generation for the nation, through quality and sustainable midwifery services. This research is to see the effect of E-ProfBid Application training on knowledge of clinical skills for midwifery care during childbirth. Type of quantitative research. The results of the Wilcoxon analysis with α = 0.05, obtained a ρ value of 0.000 where 0.005 0.05. There is a significant influence of the E-ProfBid application on knowledge of clinical skills for midwifery care during childbirth.